2007
DOI: 10.1128/jb.00505-07
|View full text |Cite
|
Sign up to set email alerts
|

Pyocyanin Alters Redox Homeostasis and Carbon Flux through Central Metabolic Pathways in Pseudomonas aeruginosa PA14

Abstract: The opportunistic pathogen Pseudomonas aeruginosa produces colorful, redox-active antibiotics called phenazines. Excretion of pyocyanin, the best-studied natural phenazine, is responsible for the bluish tint of sputum and pus associated with P. aeruginosa infections in humans. Although the toxicity of pyocyanin for other bacteria, as well as its role in eukaryotic infection, has been studied extensively, the physiological relevance of pyocyanin metabolism for the producing organism is not well understood. Pyoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
300
1
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(315 citation statements)
references
References 78 publications
7
300
1
7
Order By: Relevance
“…Indeed, reduced PYO displays significant antimicrobial activity (27) and the ability to reduce insoluble Fe 3+ to soluble Fe 2+ (32), whereas the oxidized form can potentially function as an alternative electron acceptor (33,34). Thus, to understand the biological function of PYO, it would be valuable not only to measure PYO concentration, but also the PYO redox state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, reduced PYO displays significant antimicrobial activity (27) and the ability to reduce insoluble Fe 3+ to soluble Fe 2+ (32), whereas the oxidized form can potentially function as an alternative electron acceptor (33,34). Thus, to understand the biological function of PYO, it would be valuable not only to measure PYO concentration, but also the PYO redox state.…”
Section: Resultsmentioning
confidence: 99%
“…To examine this question, biofilms of P. aeruginosa Δphz1/2, a strain unable to produce phenazines because of deletion of both phz biosynthetic operons (26), were grown in the presence of a biologically relevant amount of exogenous PYO (33). Z-direction spatial mapping of the PYO redox ratio above the P. aeruginosa Δphz1/2 biofilm revealed a PYO electrocline, indicating that biosynthesis of PYO is not required for electrocline formation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, pyocyanin was shown to have a function in signalling, responsible for the upregulation of specific genes, such as the genes involved in ferric iron acquisition and of the operon encoding the efflux pump MexGHI-OpmD PriceWhelan et al, 2006). Recently, it was shown that phenazine-defective mutants produce wrinkled colonies and accumulate NADH in the cells (Dietrich et al, 2008;Price-Whelan et al, 2007;Wangt & Newman, 2008). Pyocyanin is the phenazine that interacts most strongly with oxygen (Wangt & Newman, 2008) and it was proposed by Price-Whelan et al (2007) that externally added pyocyanin could give electrons to molecular oxygen to reduce it to water by oxidizing internal NADH to NAD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that phenazine-defective mutants produce wrinkled colonies and accumulate NADH in the cells (Dietrich et al, 2008;Price-Whelan et al, 2007;Wangt & Newman, 2008). Pyocyanin is the phenazine that interacts most strongly with oxygen (Wangt & Newman, 2008) and it was proposed by Price-Whelan et al (2007) that externally added pyocyanin could give electrons to molecular oxygen to reduce it to water by oxidizing internal NADH to NAD. We indeed found that growth of the oxyR mutant in LB medium is restored in the presence of pyocyanin or phenazine 1-carboxylic acid.…”
Section: Discussionmentioning
confidence: 99%
“…of glucose consumption and affected the growth of C. albicans (Supplementary Figure S9). Price-whelan et al, (2007) demonstrated that pyocyanin alters the redox balance and the flow of carbon through the central metabolic routes in P. aeruginosa. These authors proposed that the superoxide radicals generated by pyocyanin can reduce the sulfhydro groups of the lipoamine cofactor from the E2 subunit of pyruvate dehydrogenase, resulting in inhibition of enzyme activity.…”
Section: Drug-resistance Proteins and Other Outer Membrane Proteins Amentioning
confidence: 99%